Statins as a preventative therapy for venous thromboembolism - Wallace, Alex; Albadawi, Hassan; Hoang, Peter; Fleck, Andrew; Naidu, Sailendra; Knuttinen, Grace; Oklu, Rahmi (Cardiovascular Diagnosis and Therapy, 2017)
The anti-inflammatory effects of statins have likely not been used to their fullest extent, particularly in reducing venous thromboembolic events. Current therapy for thrombotic events hinges on anticoagulation via heparin, warfarin or new oral anticoagulants. Interventional procedures with thrombectomy may also play a critical role. Unfortunately, thrombotic events can occur and recur despite meticulous anticoagulation therapy. Venous thromboembolism (VTE) includes both deep vein thrombosis (DVT) and pulmonary embolism (PE), two complicated and prevalent diseases that can cause chronic disease states such as post-thrombotic syndrome (PTS). In 2009 the JUPITER trial demonstrated that rosuvastatin may be effective when dealing with vascular inflammation by providing an anti-inflammatory effect. Multiple subsequent studies have looked at this association with some promising findings. The mechanism of action for statins is not entirely understood but there has been a variety of proposals and subsequent testing of inflammatory biomarkers. Additional prospective trials are needed to confirm the possible benefit of VTE reduction through an anti-inflammatory effect, but if this can be shown then statins may become a safe adjunctive therapy for VTE prevention.